Pendampingan sistem aquaponik dalam mewujudkan ketahanan pangan rumah tangga - Masruroh, Nikmatul; Anggraini, Deshinta Amelia; Saputri, Dela Aulia Ajeng; Ainiya, Nur; Sulthan, Achmad; Andinata, Agil Jauzal Firdaus; Nisa, Salsabila Aulia; Lathifani, Jasmine; Kiftiyah, Ridayatul; Suhaemi, Siti; Setiawan, Deny Arif; Sururroh, Ifana Dwi; Hamid, Abdul (Nur Science Institute, 2025)
Food security remains a major challenge in rural development, even though rural areas possess vast land and strong agricultural potential. Ideally, sufficient land ownership and farming resources should guarantee stable household food availability, yet food insecurity persists. Therefore, this community engagement program aims to: (1) map household food security potential in the village, and (2) assist residents through aquaponics training to support sustainable household food supply. The program applies the Asset-Based Community Development (ABCD) approach, which focuses on identifying and analyzing community assets, including human, natural, and financial resources; infrastructure; and social and institutional networks. The results of this asset mapping are then developed using the Business Model Canvas (BMC) to plan an effective assistance strategy. Findings indicate that agricultural, livestock, human, and infrastructure assets strongly support improvements in food security. Aquaponics can be implemented in both large and small home yards at low cost, using recycled bottles for hydroponic plants and small tanks for catfish cultivation, helping households maintain sustainable access to food.